Effect of operating parameters on performance of an integrated biomass gasifier, solid oxide fuel cells and micro gas turbine system. (April 2015) - Jia, Junxi; Abudula, Abuliti; Wei, Liming; Sun, Baozhi; Shi, Yue
Abstract: An integrated power system of biomass gasification with solid oxide fuel cells (SOFC) and micro gas turbine has been investigated by thermodynamic model. A zero-dimensional electrochemical model of SOFC and one-dimensional chemical kinetics model of downdraft biomass gasifier have been developed to analyze overall performance of the power system. Effects of various parameters such as moisture content in biomass, equivalence ratio and mass flow rate of dry biomass on the overall performance of system have been studied by energy analysis. It is found that char in the biomass tends to be converted with decreasing of moisture content and increasing of equivalence ratio due to higher temperature in reduction zone of gasifier. Electric and combined heat and power efficiencies of the power system increase with decreasing of moisture content and increasing of equivalence ratio, the electrical efficiency of this system could reach a level of approximately 56%.Regarding entire conversion of char in gasifier and acceptable electrical efficiency above 45%, operating condition in this study is suggested to be in the range of moisture content less than 0.2, equivalence ratio more than 0.46 and mass flow rate of biomass less than 20  kg h −1 . Highlights: One-dimension chemical kinetics model of biomass gasifier has been developed. Un-reacted char have been predicted along the height of the reduction zone of gasifier. Effects of process parameters on char flow rate and efficiencies of BG, SOFC and GT system have been examined. Regarding entire char conversion and acceptable system efficiency, the operating condition has been proposed.